CONSUMER ATTITUDES AND HABITS ABOUT PRODUCTS WITH GEOGRAPHICAL INDICATION IN SERBIA - Miloš Ćirić; Ivana Ćirić; Tatjana Pivac; Snežana Besermenji (Ekonomika Poljoprivrede (1979), 2023)
To market products with geographical indications in the best possible way, it is necessary to examine the attitudes and habits of consumers. The subject of this paper is a survey on habits and attitudes of consumers about products with GI in Serbia. The aim of this paper is to examine the level of familiarity, attitudes, and habits of consumers, as well as to determine the knowledge and interest in these products. Citizens of Serbia participated in the research (n = 399). The methodology is based on a questionnaire that obtained the data that were processed via t-test statistical methods for independent samples, one-factor analysis of variance, the χ² test, and Pearson’s correlation coefficient. Based on the conducted research, it can be stated that about 70% of respondents are willing to pay a higher price for these products.